Implementasi Kurikulum Merdeka pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan di Sekolah Menegah Kejuruan - Pratami, Viona Amaliah; Elfizon, Elfizon (Jurnal Pendidikan Teknik Elektro, 2024)
SMK Negeri 1 Padang is one of the vocational schools that has implemented an independent curriculum since 2022. This research aims to determine the implementation of the independent curriculum in basic electricity subjects at SMKN 1 Padang. This research uses quantitative research methods with a descriptive approach. The population of this study were all teachers of basic electricity subjects at SMKN 1 Padang and all class X students at SMKN 1 Padang. The sampling technique uses proportional random sampling technique. The sample used in this research was 34 students plus 3 teachers, the total sample in this research was 37 samples. In this research, the required data collection was carried out using a questionnaire. Conclusion The results of the analysis of the effectiveness of implementing the independent curriculum in Basic Electricity subjects for teachers show that the effectiveness of implementing the independent curriculum is in the good category, this is reflected in the results obtained, namely cumulatively in the strong/effective category and descriptive statistical calculations are quite effective. The results of the analysis of the effectiveness of implementing the independent curriculum in the Basic Electricity subject for students showed that the effectiveness of implementing the independent curriculum in the Basic Electricity subject was in the good category, this is reflected in the results obtained, namely that cumulatively it was in the strong/effective category and the results of descriptive statistical calculations were sufficient effective.